STRATIFIKASI PEMAHAMAN DAN PRAKTIK DIGITAL MARKETING PADA UMKM: STUDI KUALITATIF TERHADAP PERBEDAAN TINGKAT KEMAMPUAN USAHA PEMULA, MIKRO, DAN MENENGAH - Retnowati, Novita (Growth, 2025)
This research analyzes the stratification of understanding and practices of digital marketing in Micro, Small, and Medium Enterprises (MSMEs) based on the capability levels of beginner, micro, and medium enterprises. Using a descriptive qualitative approach, this study involved nine MSME practitioners selected through purposive sampling from various business sectors. Data collection techniques employed in-depth interviews exploring six main dimensions: conceptual understanding, implementation experience, learning sources, benefit perception, implementation challenges, and mentoring experience. The research findings reveal significant stratification patterns where beginner levels demonstrate instrumental understanding with sporadic implementation through simple platforms, micro levels show evolution toward strategic approaches with multi-platform implementation, while medium levels exhibit maturity in holistic understanding with sophisticated omnichannel implementation. Learning sources show progression from informal methods to professional learning, while benefit perception develops from fundamental to strategic aspects. Challenges faced become increasingly complex with rising business capability levels, from basic technical barriers to sustainability and technology adaptability challenges. This research contributes theoretically to understanding technology adoption patterns in MSMEs and practical implications for developing differentiated empowerment programs according to business capabilities